Solar Energy for Water Optimization: Advancing Clean Water Distribution at Universitas Samudra - Abdullah, Nasruddin A; Syahri, Alfi; Amir, Fazri; Harmin, Amalia; Umar, Hamdani (Universitas Diponegoro, 2023)
The use of solar energy has become increasingly popular in recent years due to sustainability and environmental benefits. Universitas Samudra is designing the centralization of water distribution using solar energy as an energy resource. By using solar energy, universities can reduce their carbon footprint and energy costs while improving access to clean water for students, staff, and the surrounding community. This paper explores the benefits, challenges, design, and optimization of solar energy in pure water distribution, focusing on the technical and optimization of implementing such systems. The optimization is based on the water demand analysis and water source regarding the rainwater harvesting, then distribution points, including time patterns, peak demands, and seasonal fluctuation. The analyzing variables include the flow and residual head at each point distribution, pressure drop, pipe sizing, storage tank sizing, and water supply capacity input to each storage tank. The data is also based on the university's master plan and blueprint for the next 30 years of Development. Furthermore, the data will be analyzed and calculated to obtain optimum distribution pump capacity and pump working hours. The system was Analysed and calculated using Epanet hydraulic modeling software. The calculations result are that the distribution pump capacity is 16 L/s, the head is 30 M, the works for five hours a day, the power is 4.7 kW, the total energy is around 23.5 kWh per day, and The solar panel is eight kWp